2018
DOI: 10.1159/000485833
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Infrapatellar Fat Pad Volume Change to Body Weight Loss or Gain: Data from the Osteoarthritis Initiative

Abstract: Obesity is a potent risk factor for knee osteoarthritis (OA) that is driven by mechanical and potentially endocrine mechanisms, and it affects women more frequently than men. The infrapatellar fat pat (IPFP) represents a potential link between obesity, intra-articular inflammation and structural pathology. Here we investigate whether the IPFP is responsive to body weight loss/gain in women and how its responsiveness to weight change compares to that of subcutaneous fat (SCF) of the thigh. All female participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…In two large OA RCTs, Messier et al 51 and Nicklas et al 52 have reported that weight loss reduced inflammation by lowering circulating concentrations of IL-6. When assessing the IPFP, both Murillo et al 26 and Steidle-Kloc et al 31 found that weight loss is associated with a significant size reduction. A cross-sectional study by Ballegaard et al 53 examining people with overweight and knee OA using dynamic contrast-enhanced MRI found that severe perfusion/ inflammation in the IPFP was associated with more severe pain in knee OA using the KOOS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In two large OA RCTs, Messier et al 51 and Nicklas et al 52 have reported that weight loss reduced inflammation by lowering circulating concentrations of IL-6. When assessing the IPFP, both Murillo et al 26 and Steidle-Kloc et al 31 found that weight loss is associated with a significant size reduction. A cross-sectional study by Ballegaard et al 53 examining people with overweight and knee OA using dynamic contrast-enhanced MRI found that severe perfusion/ inflammation in the IPFP was associated with more severe pain in knee OA using the KOOS.…”
Section: Discussionmentioning
confidence: 99%
“…Using 1.5T MRI, one study 26 found a significant reduction in Infrapatellar fat pad (IPFP) volume in all weight loss intervention groups with a maximum of À5.2% reduction (95% CI À3.5, À7.5%). Assessed with 3T MRI, another study 31 found that >10% weight loss was correlated with a significant reduction in IPFP volume of À2.2% (SRM ¼ 0.38).…”
Section: Infrapatellar Fat Pad (Ipfp)mentioning
confidence: 97%
See 2 more Smart Citations
“…The overall pattern of FA modifications observed in the rabbits is not unique to this model, as similar changes have been documented in adipose tissue during food deprivation of rodents [36], supporting the present FA results in the rabbits with a slightly negative energy balance compared to the initial body mass. The IFP has been assumed to be resistant to starvation [4], but recent data have shown that its volume can decrease due to weight loss [38]. The effects of OA on the composition of the IFP have not been studied systematically.…”
Section: Discussionmentioning
confidence: 99%